Capital Mobility and Tax Competition: A Survey - Clemens Fuest; Bernd Huber; Jack Mintz (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper surveys the literature on the implications of international capital mobility for national tax policies. Our main issue for consideration in this survey is whether taxation of income, specifically capital income will survive, how border crossing investment is taxed relative to domestic investment and whether welfare gains can be achieved through international tax coordination. We develop a a working horse model of multinational investment which allows to derive many of the key results from the literature on international taxation in a unified framework. Moreover, we put special emphasis on the problem of tax competition and financial arbitrage.
Keywords: 330; tax competition; capital mobility; tax policy